Strategi Pengelolaan Human Capital dalam Mengatasi Stres Kerja dan Lingkungan Kerja Terhadap Peningkatan Kinerja Karyawan di PT Garuda Indonesia Cabang Bali - Hilma Harmen; Yohana Br Sinaga; Ariel Immanuel Panjaitan; Al Ikhwan; Jelita Tampubolon; Lasria Sitorus; Sabrina Theresia Sukma (IKRAITH-EKONOMIKA, 2025)
This article aims to formulate an effective human capital management strategy to address work stress and improve the work environment to enhance employee performance at PT Garuda Indonesia Bali Branch in the post pandemic period. This study uses a qualitative approach in the form of a conceptual review and primary data analysis sourced from previous research, statistical data, and contextual information from national media reports. The research results of this article indicate that work stress has a negative and significant effect on employee performance, while the work environment has a positive influence. Based on these findings, this article integrates empirical data with theoretical studies to produce an evidence-based human capital strategy framework consisting of four main pillars: improving employee well-being and mental health, strengthening work culture and internal communication, developing a potential based performance management system, and enhancing competency through continuous training. These four strategies complement each other and are designed to build organizational resilience while continuously improving employee performance. This article contributes a conceptual model that can be used as a basis for formulating human resource management policies in service organizations, particularly the aviation industry.